The Implications of the Russo-Ukrainian War on Food Security in Iraq - الشامي, حسين علي عويش; مهدي, ساره صالح (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research discusses the repercussions of the war between Russia and Ukraine on global economic and food security, with a focus on potential effects on foreign trade. It examines the economic reforms in Russia and its transition to a market economy after the collapse of the Soviet Union, impacting the country's developmental trajectories. The research also reviews the Ukrainian economic reality and its strategic importance, emphasizing the analysis of potential repercussions of the war on food security for the Iraqi economy. The research is divided into three main axes: the reality of the Russian economy between two stages, analyzing the reality of the Ukrainian economy and its strategic importance, and the repercussions of the Russian-Ukrainian war on food security for the Iraqi economy